Perancangan Alat Pres Baglog Jamur Tiram dengan Metode Quality Function Deployment (QFD) - Ramadhan, Faizal Rizki; Tjahyono, Rudi (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Mushrooms are one type of popular food ingredient and are in great demand by the public. However, the increasing demand for mushrooms is often difficult to meet because the cultivation process is still carried out conventionally, which takes quite a long time. Therefore, this study aims to design a tool that can help the baglog compaction process using a machine. In the process of designing a baglog press tool, the Quality Function Deployment (QFD) method is used. The initial stage in this study is to identify consumer needs, which are then implemented in the preparation of the House of Quality (HOQ). Based on the HOQ results, the components with the highest weight include an electric motor drive with a value of 100%, an easy operating system with a weight of 64%, and a lightweight main frame with a weight of 64%. From this study, a tool design was obtained with dimensions of 102 cm high, 80 cm long, and 60 cm wide.